Extending the Limits in Optical-Fiber Design for Higher Power Applications Using Inverse Transmission-Line Techniques - Boucouvalas, Anthony C.; Thraskias, Christos A. (IEEE journal of selected topics in quantum electronics, 2016)
In this paper, we present a new and efficient algorithm for the exact synthesis of large-mode-area (LMA) single-mode (SM) optical fibers supporting "perfect top-hat" modal electric-field profiles. We develop a technique for calculating directly and accurately the refractive-index profiles of such fibers from the knowledge of the top-hat modal electric field. The method we use to solve this inverse problem is via modeling the waveguide transversely as a transmission line. We demonstrate this algorithm with a number of example reconstructions of LMA SM optical fibers with perfect "top-hat" electric-field profile and an effective mode area (Aeff) size that in some cases exceeds 4000 μm 2 . Such fiber designs reduce or suppress the nonlinear effects, such as stimulated Brillouin scattering, stimulated Raman scattering, and self-phase modulation, in high-power applications. Moreover, we expect this LMA SM top-hat fiber design to be useful in optical-damage mitigation. Last but not the least, these "perfect" top-hat electric field profiles are very promising in the field of high-power applications for achieving uniform intensity deposition on the target (material, biological tissue, etc.)